Vulnerable Workers in an Emerging Middle Eastern Economy: What are the Implications for HRM? - Connell, Julia; Burgess, John (Routledge, 2013)
Dubai offers an example of the contradictions and tensions surrounding a development model based on migrant labour, foreign investment and a segmented labour market which has led to the exclusion of large segments of the labour force from basic forms of labour standards and protection. Unlike many other developing economies, Dubai does not possess large labour surpluses and a large informal labour market, but instead has constructed its labour market around distinct divisions within the workforce. Consequently, it is argued that, in line with building and developing civil institutions in the Middle East, there are several urgent labour reforms that are required to address the migrant workforce vulnerability and exclusion. This paper outlines the implications of these proposed reforms for human resource management (HRM) in Dubai, offering a framework that encompasses the responses required of strategic international HRM in combination with recommended human resource practices that can assist in reducing worker vulnerability.